Urokinase-loaded cyclic RGD-decorated liposome targeted therapy for in-situ thrombus of pulmonary arteriole of pulmonary hypertension - Li, Jingtao; Zhang, Xiaofeng; Mo, Yingying; Huang, Tongtong; Rao, Huaqing; Tan, Zhenyuan; Huang, Liuliu; Zeng, Decai; Jiang, Chunlan; Zhong, Yanfen; Cai, Yongzhi; Liang, Binbin; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Backgroud: In-situ thrombosis is a significant pathophysiological basis for the development of pulmonary hypertension (PH). However, thrombolytic therapy for in-situ thrombus in PH was often hampered by the apparent side effects and the low bioavailability of common thrombolytic medications. Nanoscale cyclic RGD (cRGD)-decorated liposomes have received much attention thanks to their thrombus-targeting and biodegradability properties. As a result, we synthesized urokinase-loaded cRGD-decorated liposome (UK-cRGD-Liposome) for therapy of in-situ thrombosis as an exploration of pulmonary hypertensive novel therapeutic approaches. Purpose: To evaluate the utilize of UK-cRGD-Liposome for targeted thrombolysis of in-situ thrombus in PH and to explore the potential mechanisms of in-situ thrombus involved in the development of PH. Methods: UK-cRGD-Liposome nanoscale drug delivery system was prepared using combined methods of thin-film hydration and sonication. Induced PH via subcutaneous injection of monocrotaline (MCT). Fibrin staining (modified MSB method) was applied to detect the number of vessels within-situ thrombi in PH. Echocardiography, hematoxylin-eosin (H & E) staining, and Masson's trichrome staining were used to analyze right ventricular (RV) function, pulmonary vascular remodeling, as well as RV remodeling. Results: The number of vessels with in-situ thrombi revealed that UK-cRGD-Liposome could actively target urokinase to in-situ thrombi and release its payload in a controlled manner in the in vivo environment, thereby enhancing the thrombolytic effect of urokinase. Pulmonary artery hemodynamics and echocardiography indicated a dramatical decrease in pulmonary artery pressure and a significant improvement in RV function post targeted thrombolytic therapy. Moreover, pulmonary vascular remodeling and RV remodeling were significantly restricted post targeted thrombolytic therapy. Conclusion: UK-cRGD-Liposome can restrict the progression of PH and improve RV function by targeting the dissolution of pulmonary hypertensive in-situ thrombi, which may provide promising therapeutic approaches for PH.